Isolasi Bakteri Methicillin Resistant Staphylococcus aureus pada Gagang Pintu Gedung Kampus X di Jakarta - Pasaribu, Donna Mesina Rosadini; Kelvin, Kelvin; Timotius, Kris Herawan (Universitas Kristen Krida Wacana, 2024)
Bacteria are one of the component parts in every ecosystem. Staphylococcus aureus (S. aureus) is a normal surface flora of the human body, as a temporary contaminant on inanimate objects such as clothing, cutlery and doorknobs, but also a oportunistic even pathogen on the host. The mutated strain of S. aureus has a cross-resistant strain against all antibiotics of the Beta Lactam, Methicillin, Oxacillin and Flucloxacillin groups, called Methicillin Resistant Staphylococcus aureus (MRSA). This research is needed because MRSA is a strain of bacteria that can be everywhere, especially in public facilities, such as doorknobs, which can be a place of transmission (transfer) of bacteria from one host to another. The samples in this study were taken by swabbing from the door handle in building X, Jakarta. A total of 62 samples were then cultured on Mannitol Salt Agar (MSA) media, the growing isolate was tested by Gram staining, catalase test, and mannitol. Isolate suspected of Staphylococcus aureus, ascertained whether MRSA strain using 30 μg antibiotic C efoxitin (fox) disc. The results of this study showed that 58 (87%) isolates were Staphylococcus aureus and sensitive to C efoxitin antibiotics, 8 (13%) isolates, mnitol test negative, sensitive to Ceroxitin antibiotics. The study concluded that the bacterial isolate found was Staphylococcus aureus sensitive methicillin (MSSA), no MRSA was found.